Information technology development in Lithuania: New tendencies and perspectives - Paliulis, Narimantas; Elskytė, Vida; Merkevičius, Juozas; Trasauskas, Edmundas (Journal of Business Economics and Management, 2003)
The goal of this study is to analyse processes which effect Lithuania's economical and political development, to present various expert opinions, describe tendencies and advantages of the information technologies (IT) integration in to Lithuania's daily life. Recently started development of information society is the source of different contradictions and opinions, so these opinions are presented. To better understanding of present processes in Lithuania and forecast future trends we shortly introduced progress of IT in Lithuania. The factors which will stimulate development of IT in Lithuania are also described. The IT integration processes in to separate business and social fields such as Education, Economics (Transport and communication, Electronic and electrical engineering, Chemical industry etc.), Government activity are analysed in this article. The suggestions on Lithuania's future development trends are proposed.First Published Online: 14 Oct 2010